Respostas

2014-07-21T15:22:42-03:00
X²-6x+9=0 a=1 b=6  c=9 =b2-4.a.c =(6)2 -4.1.9 =36-36 1
ali no B=6 no caso seria b=-6
ai vc coloca
mais o valor ta certo
atá ok obg
de nada
A melhor resposta!
  • Usuário do Brainly
2014-07-21T16:29:52-03:00
x²-6x+9=0

Δ= b² -4ac
Δ = (-6)² -4. 1 . 9
Δ = 36 - 36
Δ = 0

x =(-(-6) + 
√0)/ 21             x = ((-6) - √0  )/2
x = (6 + 0)/2                     x = (6 - 0) / 2
x = 6/2                               x = 6/2
x = 3                                   x = 3

S = { 3 }

1 5 1